Porównania w dwóch XVI-wiecznych poradnikach pedagogicznych – w poszukiwaniu zależności - Gozdek, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article discusses potential dependences between two pedagogical books printed in the sixteenth century: Księgi o wychowaniu i ćwiczeniu każdego przełożonego [Books on upbringing and training every superior] […] by Reinhard Lorichius and Książki o wychowaniu dzieci [Books on upbringing children] […] by Erazm Gliczner. The subjects of this study are comparative structures extracted from those books. Nineteenthcentury researchers had doubts as to the originality of Gliczner’s book. The analysis carried out for that purpose proved them to be unfounded. We can show common comparatum in only nine cases. The dependences between comparisons resulted from different comparandum or tertium comparationis. The similarity between Gliczner and Lorichius is noticeable in only one comparison.